On the identity of the rare Fragilaria subconstricta (Fragilariaceae), with Fragilaria species forming ribbon-like colonies shortly reconsidered - David Heudre; Carlos Wetzel; Laura Moreau; Bart Van de Vijver; Luc Ector (Plant Ecology and Evolution, 2019)
Background and aims – During phytoplankton surveys of a freshwater pond in Northeastern France, Fragilaria subconstricta (Bacillariophyceae) was observed. This rare diatom was present in large numbers in several plankton samples from Lachaussée Pond in the French Grand Est region.Methods – The morphology of Fragilaria subconstricta was examined in detail using light and scanning electron microscopy. Its identity is discussed and it is compared to the morphologically most similar species, especially Fragilaria capucina, F. mesolepta Rabenhorst, F. neointermedia and F. tenuistriata.Key results – Fragilaria subconstricta produces ribbon-like colonies and has narrow linear-lanceolate valves with slightly rostrate ends. The central area is rectangular, usually small or even absent. Spatulate linking spines are present all along the valve margins and a single rimoportula is located near one apex at the valve face-mantle junction. An amended diagnosis and new synonyms are proposed for this species. Additionally, the type material of Fragilaria mesolepta and a population of the very rare species Fragilaria capucina have been investigated and illustrated.Conclusions – Fragilaria subconstricta and F. tenuistriata are synonyms. Fragilaria capucina s. str. is a rare species in Europe, and the majority of records for this species should be considered part of the Fragilaria capucina “Sippenkomplex” sensu Krammer & Lange-Bertalot (1991).